INVESTIGATION OF LANE–LEVEL GNSS POSITIONING OF VEHICLE IN URBAN AREA - Akhmedov, Daulet; Moldabekov, Meirbek; Yeryomin, Denis; Zhaxygulova, Dinara; Kaliyeva, Rimma (Journal of Applied Engineering Science, 2021)
High quality GNSS (Global Navigation Satellite System) positioning can be useful for numerous engineering tasks, for example, in transport applications concerned to monitoring and optimization of road traffic. In this case lane-level positioning is a relevant task and its solution should satisfy a wide range of users, and thus should be low-cost and easy to use. In this paper the solution of accurate GNSS positioning of the car with the use of differential correction of navigation data in order to provide positioning by the lane level in urban areas of Kazakhstan is investigated. A smartphone is considered as low-cost navigation aid. Navigation data obtained using a smartphone were differentially corrected using the developed software of the Control System for Reference GNSS Station Network relative to one reference station. It is shown that using a smartphone as a navigation aid with further differential correction of data relative to one reference station allows positioning vehicles in motion with an error of 1.4 meters. The result is valuable as a basis for developing intelligent transportation systems.
Keywords: high accuracy positioning; lane-level positioning; differential GNSS; vehicle navigation